As representações sociais dos jovens do campo acerca de suas escolas - LOPES, Wiama de Jesus Freitas (2008)
This article aimed study the social representations of the country about it´s schools in the municipality of Bragança-PA. It had as central issue analyze the ways that happen interferences of the social representations of the youngsters of the country, about their schools, towards the practices of inclusion-exclusion of the educational action started in the country schools. For that, this research was based on the theory of social representations for the structuration of it’s theoretical-methodological references of data collection and treatment of curricular studies in a progressist conception, realized by the social movements currently linked to the struggle for land. In this work, there is also an incursion around the structural living conditions and the definition about being a youngster in the country. As well as there are concept researches related to the education in the country and afterwards the necessary social function of the schools in the country. The curricular, infrastructural and civil administration limitations of the educational unities in the country are some of the forgotten issues in this production for being presented as an element of constitution of social representations of the youngsters of the country about their schools. This study was developed with the objective of contributing for the improvement of the living conditions of the people of the country, aiming resignify some curricular practices strained in the inclusion-exclusion relations, outbroken in the educational action towards the youth of the country.